Corporate Cultures Of Malaysian And Foreign-Owned Firms And Their Impact On Organizational Performance - Lee, Min Ching (2006)

(untitled)
Kajian mengenai budaya firma dan pengaruhnya terhadap keuntungan organisasi kebanyakannya dari Negara Barat.